The development of AI and its impact on business models, organization and work - Lucrezia Fanti; Dario Guarascio; Massimo Moggi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2020)
This project explores the development of Artificial Intelligence (AI) and its impact on business models, market structure, organization and work. By adopting a history-friendly perspective, the present contribution traces a stylized history of the AI technological domain in order to highlight moments in time, places and sectoral domains that fostered its diffusion and transformative potential. Some descriptive analyses are also provided to investigate the diffusion of AI technologies and, at the same time, the underlying industrial and market dynamics.
Keywords: O1; O14; O15; 330; Artificial intelligence; industrial dynamics; work organization